The Role of Good Corporate Governance in Improving Company Financial Performance - Wahyu Febri Ramadhan Sudirman; Muhamamd Syaipudin (General Multidisciplinary Research Journal, 2026)
Introduction: Good Corporate Governance (GCG) is considered a key factor in enhancing firm value and ensuring sustainable business performance, particularly for companies included in the LQ45 index. Effective governance mechanisms are expected to strengthen market confidence and improve financial outcomes. This study aims to examine the impact of GCG mechanisms on firm value proxied by Tobin’s Q. Methods: This research employs a quantitative approach with a causal design. The sample consists of 30 LQ45 companies listed on the Indonesia Stock Exchange during 2015–2019, resulting in 150 firm-year observations. The independent variables include Woman on Board (WD), Committee Audit (CA), Board of Directors size (BoD), Board of Commissioners size (BoC), and Board Diversity (BD), with Company Size (SZ) and Leverage (LV) as control variables. Secondary data were obtained from annual reports and analyzed using panel data regression at a 5% significance level. Results: The findings indicate that Woman on Board (WD) has a positive and significant effect on Tobin’s Q, suggesting that female representation enhances firm value. Committee Audit (CA) and Board Diversity (BD) show significant negative effects. Board Size (BoD) and Commissioner Size (BoC) do not significantly influence firm value. Company Size (SZ) has a positive and significant effect, while Leverage (LV) is not significant. Conclusion and Suggestion: The results imply that governance effectiveness depends on quality rather than structure alone. Firms should strengthen substantive governance practices. Future studies may include additional governance indicators and extended observation periods.